Analisis Faktor-Faktor Penyebab Rendahnya Literasi Bahasa Membaca Kelas 3 Di SDN Ciledug 02 - Frima Armedia Rani Atmaja; Otib Satibi Hidayat; Indah Wardatussa’idah (CV. Ulil Albab Corp, 2026)
This study aimed to describe the factors causing low language literacy among third-grade students at SDN Ciledug 02 Bekasi Regency, explain why students’ literacy levels remain low despite the implementation of language learning programs, and identify effective instructional strategies to improve students’ language literacy skills. This research employed a qualitative approach using a case study method. The participants consisted of teachers, third-grade students, and parents. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students’ low language literacy skills were influenced by both internal and external factors. Internal factors included low reading interest, low learning motivation, and limited basic reading and writing skills. External factors consisted of inadequate family support, uncontrolled use of technology and digital media, less varied literacy teaching strategies, and limited literacy facilities and infrastructure at school. In addition, the school literacy program tended to be routine-based and had not fully engaged students in meaningful literacy activities. This study recommends that teachers and schools continuously enhance students’ language literacy competencies through the implementation of various effective instructional strategies.